The Tories From Winston Churchill to David Cameron - Heppell, Timothy (Bloomsbury Academic, 2014)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. This book offers a comprehensive and accessible study of the electoral strategies, governing approaches and ideological thought of the British Conservative Party from Winston Churchill to David Cameron. Timothy Heppell integrates a chronological narrative with theoretical evaluation, examining the interplay between the ideology of Conservatism and the political practice of the Conservative Party both in government and in opposition. He considers the ethos of the Party within the context of statecraft theory, looking at the art of winning elections and of governing competently. The book opens with an examination of the triumph and subsequent degeneration of one-nation Conservatism in the 1945 to 1965 period, and closes with an analysis of the party's re-entry into government as a coalition with the Liberal Democrats in 2010, and of the developing ideology and approach of the Cameron-led Tory party in government.